An increase of human immunodeficiency virus infection amongs blood donor during COVID-19 pandemic - Muflikhah, Nina Difla; Nuraini, Fatia Rizki (International Journal of Public Health Science (IJPHS), 2023)
Human immunodeficiency virus (HIV) is a one of crucial concern to blood safety because of their prolonged presence in the blood. Unsafe blood transfusion from infected donor contribute to spread the virus as well. Indonesia health ministry reported that HIV infection increase significantly in 2019 to 2021, and HIV case diagnose in population still way from the prediction in 2020, only 78.7% cases reported from 90% prediction case. A retrospective cross-sectional study was conducted and collected 51,351 blood donors during COVID-19 pandemic, 2020-2021. Blood sample analyzed using serological methods to detect the present of HIV antibodies. A reactive result of HIV screening from 21,260 donor in 2020 showed 12 donors reactive (0.00056%), while in 2021 from 30,091 donor showed 42 donors reactive (0.142899%) and showed a significant different from 2020 and 2021 (p-value <0.05). The number of reactive donors increase numerously from 2020 to 2021, while total donor also increased. The level of social restriction has contribution of HIV reactive case among blood donor and showed from two years of pandemic with p-value <0.05. A significant increase of HIV infection among blood donor and the effect of restriction level to prevent COVID-19 transmission are clearly show in this study.